2016
DOI: 10.1186/s12893-016-0147-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical score to predict the risk of bile leakage after liver resection

Abstract: BackgroundIn liver resection, bile leakage remains the most common cause of operative morbidity. In order to predict the risk of this complication on the basis of various factors, we developed a clinical score system to predict the potential risk of bile leakage after liver resection.MethodsWe analyzed the postoperative course in 518 patients who underwent liver resection for malignancy to identify independent predictors of bile leakage, which was defined as “a drain fluid bilirubin concentration at least thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 29 publications
0
24
0
1
Order By: Relevance
“…Kilic et al [ 18 ] suggested that, when the mass diameter was adopted as 7.5 cm, the sensitivity and specificity for biliary-cyst communication were 79% and 73%, respectively. Other authors [ 9 ] have found that a lesion size greater than 10.5 cm is a vital predictor of cyst-biliary communication. When HAE masses are large or invade the hepatic portal vessels, various blood vascular complications occur, including the vena–cava syndrome, Budd–Chiari syndrome, and jaundice obstructive or bile duct dilatation due to narrowing of the hepatic veins [ 27 ] or inferior vena cava [ 28 ] or hilar bile duct, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kilic et al [ 18 ] suggested that, when the mass diameter was adopted as 7.5 cm, the sensitivity and specificity for biliary-cyst communication were 79% and 73%, respectively. Other authors [ 9 ] have found that a lesion size greater than 10.5 cm is a vital predictor of cyst-biliary communication. When HAE masses are large or invade the hepatic portal vessels, various blood vascular complications occur, including the vena–cava syndrome, Budd–Chiari syndrome, and jaundice obstructive or bile duct dilatation due to narrowing of the hepatic veins [ 27 ] or inferior vena cava [ 28 ] or hilar bile duct, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 , 29 ] The greater the cut surface area of hepatectomy, the greater the damage to the small bile ducts. Kajiwara et al [ 9 ] set up a risk score model and revealed that the weight of the resected specimen ( P = .02) and nonanatomical resection ( P < .001) were independent predictors of postoperative BL. On the other hand, with a greater amount of blood loss, bile duct ischemia may ignore potential bile leak sites for surgeon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The postoperative biliary leak is a recognized complication of hepatobiliary and pancreatic surgery, with a reported frequency ranging from 0.5% to 15.6% [ 1 , 2 7 ]. Independent risk factors for postoperative biliary leak include preoperative cholangitis, complex hepatectomy, and a long operating time [ 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Под билиарными осложнениями понимают нарушение герметичности желчных протоков после нарушения их целостности. Следствием желчеистечения может быть развитие биломы, желчного свища и желчного перитонита [1][2][3].…”
unclassified